Evaluación del comportamiento agronómico de dos híbridos experimentales promisorio de maíz en tres localidades del litoral ecuatoriano y una en los valles sub tropicales de la provincia de Loja - Campuzano Hidalgo, Mayusbell (2019)
An essay has been stablished based on the four contrasting environments that Ecuador’s coast has and one from the sub-tropical zone of Loja, during the rainy season in the year 2019, with the goal of evaluating and comparing, two promissory corn hybrids and versus seven commercial hybrids with high performance and desirable agronomic characteristics. The genetic material consisted on two promissory hybrids from INIAP, compared with seven commercial witnesses. A random experimental design of the blocks with three repetitions was used for each environment. The experimental allotments we two 5m long grooves spaced by 0, 80 and 0, 20. An analysis of variation of environment has been made and a combinations of those environments. Consequently, a Turkey test at 5% was made to determine the range of signification. Therefore with the goal of estimating the adaptation and results, we used a qualitative method by applying the media and standard deviation; the analysis of variations determined statistical differences in the sources of variation and the variables of study, indicating the differential response of hybrids to different environments. The commercial hybrids registered a maximum performance of 6,50 t/ha while other promissory hybrids reported an average performance of 5,10 t/ha